Comparison of variaton in extract concentration onion leaf (Allium fistulosum L.) to mortality larvae Aedes aegypti mosquito instar III - Wulandari, Siska; Lukiyono, Yauwan Tobing; Andini, Ary; Nidianti, Ersalina (Universitas Nahdlatul Ulama Surabaya, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the Dengue virus which is transmitted through the Aedes aegypti mosquito. DHF is caused by the Dengue virus whose main vector is the Aedes aegypti mosquito and the secondary vector is the Aedes albopictus mosquito. Eradicating Aedes aegypti and Aedes albopictus is one way that can be done to prevent the spread of the Dengue virus. Control of the dengue vector can be carried out on larvae and adult mosquitoes with the aim of breaking the chain of transmission. One way that can be done is by using a natural larvicide which utilizes the Allium fistulosum plant which contains secondary metabolite compounds including phenolics, flavonoids and tannins which can kill larvae. This study aims to determine the comparison of variations in the concentration of Allium fistulosum leaf extract on the mortality of Aedes aegypti instar III. The type of research used in this research was experimental with a completely randomized design (RAL). The potential level of the extract is reviewed from the Lethal Concentration (LC50) and Lethal Time (LT50) values. The data obtained were analyzed using a probit regression test or probit analysis to determine the potential of Allium fistulosum extract as an alternative larvicide for third instar Aedes aegypti larvae and stated as Lethal Concentration (LC50) and Lethal Time (LT50) with a confidence level of 95.0%. The results of the research show that Allium f istulosum leaf extract has the potential as an alternative larvicide for the death of third instar Aedes aegypti larvae as proven by a p-value of 0.000 (< 0.05) with a value of LC50-6 hours is 52.850%, LC50-8 hours is 42.674%, LC50-24 hours is 30.900%, LT50-20% is 37.674 hours, LT50-30% is 24.423 hours and LT50-40% is 14.954 hours.